2016
DOI: 10.3390/ijerph13101008
|View full text |Cite
|
Sign up to set email alerts
|

L-Asparaginase Isolated from Phaseolus vulgaris Seeds Exhibited Potent Anti-Acute Lymphoblastic Leukemia Effects In-Vitro and Low Immunogenic Properties In-Vivo

Abstract: Escherichia coli-derived L-asparaginases have been used in the treatment of acute lymphoblastic leukemia (ALL), however, clinical hypersensitivity reactions and silent inactivation due to antibodies against E. coli-asparaginase, lead to inactivation of these preparations in most cases.Therefore, this study was aimed to investigate the cytotoxicity and antitumor effects ofa novel L-asparaginaseenzyme, isolated from Phaseolus vulgaris seeds (P-Asp) on the ALL cell line (Jurkat). The immunogenicity of the enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The samples were analyzed by fluorescence-activated cell sorting (FACS) as we previously described. 31 2.2.5. Reverse Transcription and Quantitative Real-Time PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were analyzed by fluorescence-activated cell sorting (FACS) as we previously described. 31 2.2.5. Reverse Transcription and Quantitative Real-Time PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis detection was performed by FITC Annexin-V/PI kit (Becton Dickenson, Franklin Lakes, NJ) following the manufacture’s protocol. The samples were analyzed by fluorescence-activated cell sorting (FACS) as we previously described …”
Section: Methodsmentioning
confidence: 99%
“…A search in the UniProt database showed that most of the homologs to L-ASNase Rhizobium etli are found in bacteria Firmicutes and Proteobacteria , and some homologs are also present in eukaryotes, including fungi Ascomycetes . L-ASNases from a variety of terrestrial microorganisms [ 153 , 154 , 155 ], plants [ 156 , 157 ] and fungi [ 158 ] have been studied; however, almost all failed to meet the strict criteria for antitumor drugs [ 159 ].…”
Section: Alternative Approaches To the Development Of Antitumor L-asn...mentioning
confidence: 99%
“…The effect on cell cycle distribution of the most efficient antitumor compound was tested, as previously described [41]. Briefly, cells were incubated with IC 50 of the test compounds for 48 h. Treated cells were detached by trypsinization, washed twice with ice-cold PBS and resuspended in 0.5 mL PBS.…”
Section: Cell Cycle Kinetics Analysismentioning
confidence: 99%